Special Issue Dedicated to ICFP 2012: Editorial. Issue 2 (21st May 2014) - SINGH, SATNAM; FINDLER, ROBERT BRUCE
<x content-type="archive" xml:space="preserve">Abstract</x> The 17th ACM SIGPLAN International Conference on Functional Programming (ICFP) took place on September 10–12, 2012 in Copenhagen, Denmark. After the conference, the programme committee selected several outstanding papers and invited their authors to submit to this special issue of Journal of Functional Programming. Robby Findler and Satnam Singh acted as editors for these submissions. This issue includes the accepted papers, each of which provides substantial new material beyond the original conference version.